Big data and the dairy cow: factors affecting fertility in UK herds - Hudson, Chris (2015)
Routinely collected herd management data in a variety of formats were collated from 468 dairy herds, and novel objective measures of data recording quality were developed and applied. This revealed that there was a substantial amount of variation in data quality between herds, and the vast majority of herds failed to meet the threshold level for at least one of the data quality measures used. Analysis of trends in reproductive performance across the herds with good quality fertility event recording suggested that their fertility was generally declining through the first half of the 2000s, but there was some evidence that improvements in submission rate were beginning to reverse this decline in the later years studied (up to 2007).